2019
DOI: 10.1002/andp.201900044
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Interference Line Shifts of Broad Dipole‐Allowed Transitions

Abstract: High-resolution laser spectroscopy serves the purpose of determining the energy difference between states of atoms and molecules with the best possible accuracy. Therefore, one may face the problem of finding the center of a symmetric line within a small fraction of the line width, or one needs to extract the energy difference from an asymmetric line without a uniquely defined center. Multiplets of atomic resonance lines are subject to mutual line pullings and give rise to asymmetric line distortions due to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Hessels and co-workers have made significant contributions toward understanding these effects [47,[56][57][58][59], and they have shown that measurements performed with an uncertainty comparable to the square of the linewidth divided by (twice) the separation of the main resonance and a neighboring (offresonant) transition may well be affected by them [55]. This "rule of thumb" [47], which has also been obtained analytically by other researchers using perturbation theory [60], gives an approximate value for the error one would obtain fitting a Lorentzian profile to a line shape distorted by QI effects. We note that in some types of measurements, line shapes are distorted via direct interference between incident and emitted radiation (e.g., [49,52]).…”
Section: Quantum Interferencementioning
confidence: 66%
“…Hessels and co-workers have made significant contributions toward understanding these effects [47,[56][57][58][59], and they have shown that measurements performed with an uncertainty comparable to the square of the linewidth divided by (twice) the separation of the main resonance and a neighboring (offresonant) transition may well be affected by them [55]. This "rule of thumb" [47], which has also been obtained analytically by other researchers using perturbation theory [60], gives an approximate value for the error one would obtain fitting a Lorentzian profile to a line shape distorted by QI effects. We note that in some types of measurements, line shapes are distorted via direct interference between incident and emitted radiation (e.g., [49,52]).…”
Section: Quantum Interferencementioning
confidence: 66%
“…Equation (21) allow us to define the four-vector potential that drives the creation of the pairs. Equation (22) simply say that charge density is the divergence of polarization and the current is the sum of its polarization and magnetization parts. Our results support the conclusion of Zeldovich, who considered a Lagrangian in which all of the electromagnetic term comes from the interaction of the particle with the field and came to an interesting interpretation [41]: in the absence of vacuum polarization, electric and magnetic fields act on Dirac fermions, but there is no field energy and no electromagnetic wave propagation.…”
Section: Connection With a Dielectric Modelmentioning
confidence: 99%
“…Such a medium may well consist of particle-antiparticle bound states, as first discussed by Ruark [12] and further elaborated by Wheeler [13]. This approach has been recently adopted [14][15][16] to obtain expressions for the permittivity, leading to ab initio calculations of the value of ε 0 and to useful discussions of the significance of those calculations [17][18][19][20][21][22]. The main assumption in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that line centers of resonances can be affected by the presence of nearby off-resonant pathways and that shifts and asymmetric line shapes can result (e.g., Refs. [11,12]). Indeed, these types of quantum interference (QI) effects have had to be taken into account in several highprecision measurements (e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%